Assessing change of direction ability in badminton athletes - Paterson, S.; McMaster, D. T.; Cronin, J. (Strength and Conditioning Journal, 2016)
This review provides a stock take of badminton-specific change of direction (cod) research and provides recommendations to practitioners for cod assessment. The review will examine relationships between cod and the following measures: anthropometry, elastic strength, concentric strength, leg muscle imbalances, technique, straight-line sprint speed, and flexibility. A badminton-specific cod assessment battery is proposed with the inclusion of 2 new tests: a multidirectional lunge test and a multidirectional cyclic cod test.